Glutathione plays a fundamental role in growth and symbiotic capacity of Sinorhizobium meliloti - Harrison, Judith (2005)
Rhizobia form a symbiotic relationship with plants of the legume family to produce nitrogen-fixing root nodules under nitrogen-limiting conditions. We have examined the importance of glutathione (GSH) during free-living growth and symbiosis of Sinorhizobium meliloti. An S. meliloti mutant strain (SmgshA) which is unable to synthesize GSH due to a gene disruption in gshA, encoding the enzyme for the first step in the biosynthesis of GSH, was unable to grow under nonstress conditions, precluding any nodulation. In contrast, an S. meliloti strain (SmgshB) with gshB, encoding the enzyme involved in the second step in GSH synthesis, deleted was able to grow, indicating that γ- glutamylcysteine, the dipeptide intermediate, can partially substitute for GSH. However, the SmgshB strain showed a delayed-nodulation phenotype coupled to a 75% reduction in the nitrogen fixation capacity. This phenotype was linked to abnormal nodule development. Both the SmgshA and SmgshB mutant strains exhibited higher catalase activity than the wild-type S. meliloti strain, suggesting that both mutant strains are under oxidative stress. Taken together, these results show that GSH plays a critical role in the growth of S. meliloti and during its interaction with the plant partner.